Supplement of 5-hydroxytryptophan before induction suppresses inflammation and collagen-induced arthritis. Issue 1 (December 2015) - Yang, Tao-Hsiang; Hsu, Peng-Yang; Meng, Menghsiao; Su, Che-Chun
Abstract Background Evidence is accumulating that a preclinical phase is present before the onset of clinical signs and symptoms of rheumatoid arthritis (RA). This phase represents an important therapeutic window within which interventions can dramatically modulate outcomes. An agent able to prevent RA for high risk individuals in this phase is therefore desired. In this study, we investigated whether tryptophan metabolite, 5-hydroxytryptophan (5-HTP) or 5-methoxytryptophan (5-MTP), can act as such an agent for primary prevention of collagen-induced arthritis (CIA). Methods Mouse splenocytes were pretreated with 5-HTP or 5-MTP and activated by anti-CD3 plus anti-CD28 antibodies in vitro. The percentages of interferon-γ (IFNγ)+ CD4+ T cells and interleukin-17 (IL-17)+ CD4+ T cells were measured by flow cytometry. The production of pro-inflammatory cytokines, serotonin and kynurenine was measured by enzyme-linked immunosorbent assay. A CIA model was used to investigate the in vivo effects of 5-HTP on the prevention of arthritis. Results 5-HTP decreased the percentages of IFNγ+ CD4+ T cells and IL-17+ CD4+ T cells and suppressed the production of IL-2, IL-4, IL-6, IL-17, tumor necrosis factor-α (TNFα) and IFNγ in activated splenocytes. 5-HTP administered before induction decreased the disease activities in CIA mice and suppressed the production of TNFα, IL-6 and cyclooxygenase-2 in arthritic joints. 5-HTP also increased serotonin, but decreased kynurenine in the CIA mice. Conclusions 5-HTP suppresses inflammation and arthritis through decreasing the production of pro-inflammatory mediators. 5-HTP supplement before induction ameliorates arthritis in a CIA model.